A horse-cloth for Uganda, or how an account by a transhumant veterinary connects histories, animal diseases and continents. (2nd January 2018) - Podgorny, Irina
ABSTRACT: The picture of a 'pony in pajamas' is used to construct the backstory of a deadly animal disease in three parts. First, by focusing on the figure of the 'author' of the cloth depicted in the picture, Scottish veterinarian Robert John Stordy, one can examine the repercussions of transhumant biographical itineraries. Second, a focus on regional epizootics helps alter scales defining the local versus the global. Third, the global circulation of mules and the medicines used to cure them illustrate displacement of objects and knowledge that shaped the understanding of sickness and its remedies. Thus, the remedies and horse-clothes used in Uganda not only speak of things and beings that linked distant geographies and contexts, they also mark the multiple hubs where these connections did occur, propelled in part by commercial interests, biographical itineraries and, of course, randomness.